Preparation of Microfiber Grating for Real-Time Sensing of Escherichia Coli Concentration - Qingyan Qiu; Min Dai; Caidong Luo; Ying Mu; Wei Du; Yu Li; Jun Luo; Rong Li (Journal of Chemistry)
Various diseases are spread by means of contaminated water or food, and the detection of pathogenic bacteria has great significance for securing a proper healthy environment for human beings. In this article, microfiber gratings (MFGs) were fabricated by using a high-frequency CO2 laser. The number of periods is 30, and the length of the period is 600 μm. A type of biosensor is proposed in this study. Results showed that the biosensor was strongly sensitive to the concentration of Escherichia coli and a maximum sensitivity of 1.15 nm/107 CFU was achieved. The mechanism of real-time sensing of prepared MFG was also proposed, which could be due to relationship between dip wavelength shift and the concentration of detected bacteria. The prepared MFGs do not need any coating, and the proposed biosensor has a great potential for application in fields of medical treatment, biology, and farming.